Report on industrial attachment with Biosensors Interventional Technologies Pte Ltd - Nashata Mohamed Isa (2012)
This report serves to provide an overview of the 22-week attachment experience with Biosensors Interventional Technologies Ptd Ltd. It emphasizes on two primary learning outcomes namely the overall structure and functioning of a biomedical company and the main projects accomplished as a Regulatory Affairs Associate. Being part of the Regulatory Affairs Department, much exposure was given from all aspects such as from the working styles of employees of other departments, technical skills attained while completing regulatory-related projects, knowledge garnered from attending seminars, trainings and meetings as well as management skills acquired while handling multiple projects at one time. Other than providing a clear picture of the technical details of the attachment experience, the later part of this report will discuss the achievements, learning outcomes and recommendations that were carved out from this attachment program.